PENGARUH PENGETAHUAN, PENDAPATAN, DAN KEPERCAYAAN, TERHADAP MINAT MUZAKKI DALAM MEMBAYAR ZAKAT DI BAITUL MAL KOTA LHOKSEUMAWE - Zul Fahmi; Mukhlish M.Nur (LPPM UNIMAL, 2018)
ABSTRACT This study aims to examine the influence of knowledge, income, and trust of muzzaki on their motivation to pay zakat at BaitulMal, Lhokseumawe. This study employs quantitative method with 75 traders at Pasar Los, Lhokseumawe, as the samples. The data were collected using questioner and were analyzed using multiple linear regression with validity test and reliability test following the analysis. The result shows that all independent variables which are identified as Knowledge (X1), income (X2), and trust (X3) simultaneously influence the dependent variable which is identified as muzakki’s motivation in paying zakat at BaitulMal, Lhokseumawe (Y). The result suggests that knowledge (X1) and trust (X3) partially influence the muzakki’s motivation in paying zakat, while income (X2) does not influence the motivation. The significance of the influence can be seen from the adjusted R square (R2) value which is realized by 32,1%, while the other 67,9% was the influence from other variables outside this study.